Biochar as smart organic catalyst to regulate bacterial dynamics during food waste composting. (April 2023) - Verma, Shivpal; Kumar Awasthi, Mukesh; Liu, Tao; Kumar Awasthi, Sanjeev; Yadav, Vivek; Ravindran, Balasubramani; Syed, Asad; Eswaramoorthy, Rajalakshmanan; Zhang, Zengqiang
Graphical abstract: Highlights: The effect of wheat straw biochar (WSB) on food waste composting was studied. Firmicutes, Proteobacteria and Bacteroidota were the dominate phyla of the treatments. Lactobacillus fermentum and Bacillus thermoamylovorans were higher abundance. Bacillus, Weissella, and Paracoccus were considered as possible biomarkers. Abstract: The impact of wheat straw biochar (WSB) on bacterial dynamics succession during food waste (FW) composting was analyzed. Six treatments [0(T1), 2.5(T2), 5 (T3), 7.5 (T4), 10 (T5), and 15 %(T6)] dry weight WSB were used with FW and saw dust for composting. At the highest thermal peak at 59 ℃ in T6, the pH varied from 4.5 to 7.3, and electrical conductivity among the treatments varied from 1.2 to 2.0 mScm 1 . Firmicutes (25–97 %), Proteobacteria (8–45 %), and Bacteroidota (5–50 %) were among the dominate phyla of the treatments. Whereas, Bacillus (5–85 %), Limoslactobacillus (2–40 %), and Sphingobacterium (2–32 %) were highest among the identified genus in treatments but surprisingly Bacteroides was in greater abundance in the control treatments. Moreover, heatmap constructed with 35 various genera in all the treatments showed that Gammaproteobacterial genera contributed in large proportion after 42 days in T6. Additionally, a dynamic shift from Lactobacillus fermentum to higher abundance of Bacillus thermoamylovorans was reported on 42 days of FW composting. Biochar 15 % amendment can improve FW composting by influencing bacterial dynamics.